A cytogenetic deletion, del(17)(q11.22q21.1), in a patient with sporadic neurofibromatosis type 1 (NF1) associated with dysmorphism and developmental delay. Issue 2 (February 1996) - Upadhyaya, M; Roberts, S H; Maynard, J; Sorour, E; Thompson, P W; Vaughan, M; Wilkie, A O; Hughes, H E
Abstract : We report the first visible cytogenetic deletion involving the NF1 gene in a patient with sporadic neurofibromatosis, dysmorphic features, and marked developmental delay. The combined evidence of molecular and cytogenetic techniques based on dosage reduction, hemizygosity for microsatellite markers, high resolution G banding, and FISH analysis, predicts this deletion to be approximately 7 Mb in size. Our findings highlight the importance of conducting a detailed cytogenetic and FISH analysis in patients with NF1 who have additional dysmorphic features or particularly severe learning difficulties.